Development of blood-brain barrier-penetrating antibodies for neutralizing tick-borne encephalitis virus in the brain - Fukuta, Mizuki; Fukano, Sayo; Maekawa, Naoya; Kobayashi, Shintaro; Okamoto, Shunsuke; Hirano, Minato; Nio-Kobayashi, Junko; Kariwa, Hiroaki; Kawakami, Shigeru; Konnai, Satoru; Yoshii, Kentaro (mSphere, 2025)
Tick-borne encephalitis virus is a neuroinvasive pathogen that causes severe neurologic disease, significantly affecting patients' quality of life. No specific antiviral treatment is available for tick-borne encephalitis caused by virus multiplication in the brain. The delivery of drugs to the brain via peripheral administration is often obstructed by the blood-brain barrier. To develop targeted antiviral therapies for brain infections, we engineered recombinant antibodies capable of crossing the blood-brain barrier via brain-targeted ligands. These antibodies exhibited permeability across the blood-brain barrier in both in vitro and in vivo models and notably effectively neutralized the virus within the brain following peripheral administration. This study is the first to highlight the therapeutic potential of brain-targeted recombinant antibodies after viral entry into the brain, offering a promising pathway for the development of effective antiviral treatments for tick-borne encephalitis.